Effects of water and nitrogen stresses on a shortgrass prairie ecosystem - Lauenroth, William K., author; Sims, Phillip L., advisor; Innis, George S., 1937-, committee member; Reid, Charles P. P., committee member; Hansen, Richard M., committee member (Colorado State University. Libraries, 1973)
Response of a shortgrass prairie ecosystem to stresses created by excess inputs of water and nitrogen were studied during a two year period in northeastern Colorado. Nitrogen stress was created by maintaining soil water potential greater than -0.8 bars during the growing season. Responses measured were net primary productivity, species composition and organization of primary producers, evapotranspiration, and small mammal densities. Net primary productivity was more responsive to water and nitrogen in combination than to either individually. Aboveground contribution to net primary productivity was more sensitive to stresses than the below-ground contribution. Ratios of above- to belowground productivity were increased by all stresses. The major effect of stresses on species composition of primary producers was to reorder existing species relationships and increase the number of species coexisting on the treatments. Primary producer organization (successional state) was assessed by diversity and dominance calculations. After two years of treatment the primary producers on the nitrogen treatment were at the highest level of organization and those of the water plus nitrogen treatment at the lowest level. Evapotranspiration of the treatments receiving additional water was close to the potential rate. The primary producers of the shortgrass prairie do not have the capacity to limit transpiration under conditions of high water availability. Small mammal species demonstrated clear habitat preferences to the treatments. The prairie vole was caught almost exclusively on the water plus nitrogen treatment. The deer mouse was captured in approximately equal proportions on the water and the water plus nitrogen treatments and in much lower numbers on the remaining treatments. The grasshopper mouse and thirteen lined ground squirrel were caught in low numbers on the water treatments an din significantly higher numbers on the control and nitrogen treatments.
Keywords: Grassland ecology; Plant-water relationships; Plants -- Effect of nitrates on